2015
DOI: 10.1073/pnas.1513913112
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine produces antidepressant-like effects through phosphorylation-dependent nuclear export of histone deacetylase 5 (HDAC5) in rats

Abstract: Ketamine produces rapid antidepressant-like effects in animal assays for depression, although the molecular mechanisms underlying these behavioral actions remain incomplete. Here, we demonstrate that ketamine rapidly stimulates histone deacetylase 5 (HDAC5) phosphorylation and nuclear export in rat hippocampal neurons through calcium/calmodulin kinase II-and protein kinase D-dependent pathways. Consequently, ketamine enhanced the transcriptional activity of myocyte enhancer factor 2 (MEF2), which leads to regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…Ketamine acutely increases hippocampal proteins brain-derived neurotrophic factor (BDNF; Garcia et al, 2008; Yang et al, 2013) and mammalian target of rapamycin (mTOR; Yang et al, 2013), which may also help to explain the mechanism for its rapid antidepressant effects. Indeed, investigation into ketamine’s antidepressant effects have led to several reports that ketamine may affect various brain regions through epigenetic mechanisms, such as histone deacetylase modulation (Reus et al, 2013; Choi et al, 2015) and increased BDNF mRNA expression (Duman and Voleti, 2012). …”
Section: Proposed Mechanisms Of Actionsmentioning
confidence: 99%
“…Ketamine acutely increases hippocampal proteins brain-derived neurotrophic factor (BDNF; Garcia et al, 2008; Yang et al, 2013) and mammalian target of rapamycin (mTOR; Yang et al, 2013), which may also help to explain the mechanism for its rapid antidepressant effects. Indeed, investigation into ketamine’s antidepressant effects have led to several reports that ketamine may affect various brain regions through epigenetic mechanisms, such as histone deacetylase modulation (Reus et al, 2013; Choi et al, 2015) and increased BDNF mRNA expression (Duman and Voleti, 2012). …”
Section: Proposed Mechanisms Of Actionsmentioning
confidence: 99%
“…52 Interestingly, blocking NMDA activity with the noncompetitive antagonist ketamine, can induce the nuclear export of HDAC5 and may represent a novel, fast-acting treatment for MDD (see below). 53 The coordinated activation and translocation of HATs and HDACs suggests that acetylated histones play a role in regulating activity-dependent neuronal transcription and may provide an interesting avenue of investigation in the etiology of neuropsychiatric illness.…”
Section: Activity-dependent Chromatin Opening Via Histone Modificationmentioning
confidence: 99%
“…Similarly, dimethylation of H3K9 and H3K27 by imipramine (Wilkinson et al, 2009) was found to be equally effective in upregulating transcription of genes which could potentially be directed towards reversing dysfunctional cognitive system. Despite the controversy related to its recreational use and abuse, ketamine has been used to stabilize the mood with a moderate dose by augmenting epigenetic alteration in neurochemical pathways with its fast mode of antidepressant function (Choi et al, 2015). Recent evidence has shown its effectiveness in moderating the impulsivity associated with suicidal ideation of mood disorder patients (Price et al, 2014; Thakurta et al, 2012).…”
Section: Future Directionsmentioning
confidence: 99%
“…An overall reversal of depressive symptom in the same study cohort found to be paralleled with the observed anti-suicidal tendency which indicated a positive role of ketamine in regulating AMPA to NMDA receptor throughput, changes in synaptic connections and enhancing the BDNF signaling (Price et al, 2014). However, a link was still missing to establish the intermediate role of ketamine as epigenetic modulator until a recent report from preclinical study pointed out HDAC5 modulation in hippocampal neurons (Choi et al, 2015). The report helped to understand ketamine’s role in rapidly stimulating histone deacetylase 5 (HDAC5) phosphorylation and nuclear export in rat hippocampal neurons with direct involvement of calcium/calmodulin kinase II- and protein kinase D-dependent pathways.…”
Section: Future Directionsmentioning
confidence: 99%